Uma proposta para sincronização de dados em dispositivos ubíquos - Paulo Henrique Lossio Barros (2008)
The omnipresence of smart phones, PDAs, smart cards, sensors and other ubiquitous devices, along with the development of different types of networks for wireless data, have led to a major shift in the use, design and development of information systems. Increasingly ubiquitous devices to access data are used as tools for work. Executives, vendors, workers in general update corporate information wherever they are. Even with the advances in technology of hardware and wireless communications networks, the disconnections are common. Devices can be disconnected for various reasons such as lack of network coverage or simply to save energy. To simulate an environment of continuous connection and maintain the appearance of ubiquity even when disconnected, the applications can anticipate the disconnection and copy some of the information available on servers connected to fixed network for the devices, which can be accessed and modified during the periods without connection. The key feature of this new paradigm of computing is the ability to store data locally on mobile clients and synchronize the changes back to the corporate server. This feature plays a key role in the vision of pervasive and ubiquitous computing, where information is available at any time and anywhere. This work proposed and implemented a framework, called mSync (mobile Synchronization), for data synchronization in ubiquitous devices. The framework deals with problems related to the query and modification of data in a distributed environment, allowing developers to use the data synchronization in their applications as a service and to focus on specific issues of implementation. The framework speeds up the development of solutions that use data replication and synchronization, providing a high level of abstraction for developers that hide the complexity introduced by distribution. We present two case studies to illustrate the effectiveness and usefulness of the framework. The first, a single application for registration of customers and sales, was developed to demonstrate the use of framework. The second case study presentes a real application of supervision of works, projects and services, used by Crea-MG, which uses the mSync as a tool to allow consultation and modification of data in disconnected mode.